An Unusual Case of Malignant Hypertension and Stress Cardiomyopathy - Anjali Rao; Wanpen Vongpatanasin (Annals of Internal Medicine: Clinical Cases)
A 39-year-old man with chronic hypertension presented with perioperative malignant hypertension while undergoing induction for elective surgery. He was treated with intravenous antihypertensives. He reported several years of episodic chest pain, palpitations, and diaphoresis. Transthoracic echocardiogram demonstrated new-onset cardiomyopathy. Urinary and serum catecholamines were measured and the pattern of catecholamine levels suggested an extra-adrenal source. Computed tomography of the abdomen showed a contrast-enhancing mass in the bladder suspicious for metastatic paraganglioma. The patient had surgical resection with substantial improvement in his hypertension. The presence of labile hypertension and acute cardiomyopathy precipitated by stress should prompt evaluation for a catecholamine-producing tumor and appropriate genetic testing.